Composition and distribution of moss formations in the ice-free areas adjoining the Arctowski region, Admiralty Bay, King George Island, Antarctica - Victoria, Filipe de Carvalho (2009)
The phytosociology of moss vegetation in the ice-free areas adjoining Polish Antarctic Station Henrik Arctowski, located at Admiralty Bay, inside the King George Island, was investigatedduring the 2002/2003 and 2003/2004 summer season. The most representative families had been Bryaceae, Polytrichaceae, Andreaeaceae and Pottiaceae. The most frequent species had been Sanionia uncinata (Hedw.) Loeske and Polytrichum juniperinum Hedw. Was possible to describe the associations of mosses in the region of Arctowski, being evidenced the occurrences of seven main formations, which it have been recognized and described twelve associations between the frequent and abundant species in the area. Here they are described along with their distribution in the area, their species richness and the diversity index for each formation found during this study.